Involvement of CETP (Cholesteryl Ester Transfer Protein) in the Shift of Sphingosine-1-Phosphate Among Lipoproteins and in the Modulation of its Functions. Issue 3 (March 2017) - Kurano, Makoto; Hara, Masumi; Ikeda, Hitoshi; Tsukamoto, Kazuhisa; Yatomi, Yutaka
Abstract : Objective—: Sphingosine-1-phosphate (S1P) is a vasoprotective lipid mediator. About two thirds of plasma S1P rides on high-density lipoprotein (HDL), and several pleiotropic properties of HDL have been ascribed to S1P. In human subjects, CETP (cholesteryl ester transfer protein) greatly influences HDL quantities. In this study, we attempted to elucidate the roles of CETP in the metabolism of S1P. Approach and Results—: We overexpressed CETP in mice that lacked CETP and found that CETP overexpression decreased the HDL level but failed to modulate the levels of S1P and apolipoprotein M (apoM), a carrier of S1P, in the total plasma. We observed, however, that the distribution of S1P and apoM shifted from HDL to apoB-containing lipoproteins. When we administered C17 S1P bound to apoM-containing lipoprotein, C17 S1P and apoM were rapidly transferred to apoB-containing lipoproteins in CETP-overexpressing mice. When HDL containing C17 S1P was mixed with low-density lipoprotein ex vivo, C17 S1P shifted to the low-density lipoprotein fraction independent of the presence of CETP. Concordant with these results, apoM was distributed mainly to the same fraction as apo AI in a CETP-deficient subject, although apoM was also detected in apo AI–poor fractions in a corresponding hypercholesterolemia subject. About the bioactivities of S1P carried on each lipoprotein, S1P riding on apoB-containing lipoproteins induced the phosphorylation of Akt (AKT8 virus oncogene cellular homolog) and eNOS (endothelial nitric oxide synthase) in human umbilical vein endothelial cells, and CETP overexpression increased insulin secretion and sensitivity, which was inhibited by an S1P receptor 1 or 3 antagonist. Conclusions—: CETP modulates the distribution of S1P among lipoproteins, which affects the bioactivities of S1P. Abstract : Supplemental Digital Content is available in the text.